EJECUCION DE OBRAS DE LA JUNTA PARROQUIAL DE RICAURTE - ARAUJO CABEZAS, JOSE ANTONIO (2018)
The parochial junta without law and without budget of 1998 was created as sectional and autonomous organisms with similar duties and attributions to the cantonal councils and provincial councils. (Regulation of the Organic Law of Parochial Boards by Executive Decree Number 1894. Registration 421 dated September 27, 2001.)